The Influence of Reinforcement to Motivate the Students in Learning Speaking - Rusnaini usman; Amzah; Magdahalena Tjalla (Inspiring: English Education Journal, 2021)
This research was conducted to examine the effectiveness of reinforcement to motivate the students in learning speaking at SMPN 3 Batulappa. kab pinrang.This research used a pre-experimental method, by one group pre-test and post-test design. There were two variables they were independent variable the use of reinforcement strategy and dependent variable that is the students’motivation in learning speaking. The population of this research was a SMPN 3 Batulappa kab.pinrang, in academic year 2019/2020 which consists of one classes. The sample of this research was take one class of the population was class VIII.1 . In collecting data on students’motivation in learning speaking The researcher given pre-test before treatment, and post-test after treatment.The result calculation of mean score pre-test of students was 37.85 and mean score post-test of students was 67.85 it showed that the students speaking was increased. The result finding that score of t-test value was 4,51 while the score of t-table value was 1.725 for the level significance 0,5 degree of freedom 20. It showed that the alternative hypothesis (Ha) was accepted, which the t-test value was greater than t-table value. Besides. It meant that the reinforcement was interested for the students in learning speaking. Based on data analysis, the researcher concluded that using reinforcement able to motivate the students in learning speaking at SMPN 3 Batulappa kab pinrang.